Application of Magic Card Media to Improve Student Learning Outcomes in Tarekh Islam Subject Class 1 KMI Modern Islamic Institution Darussalam Gontor - Nizham Mahmudi Muttaqin; Saiful Anwar; Jasirawati Jasirawati; Hajizah Indah; Ilmiya Nafi'ah; Salsabilla Nafis (Educan : Jurnal Pendidikan Islam, 2022)
Tarekh Islam is one of the important subjects that aims and seeks to shape the character and personality of the people. The history of Islam or more often referred to as Islamic Dates is material that discusses a collection of important events or events from Muslim figures. By studying this material, students can gain valuable lessons from the journey of leaders from generation to generation. Students can also imitate the good qualities of these figures. In the application of learning, although many students like the Islamic Date material, some phenomena show that this learning tends to be passive. The purpose of this study was to improve the learning outcomes of grade 1 B students on Islamic Dates material using Magic Card learning media. The research subject is class 1 B KMI Modern Islamic Institution Darussalam Gontor Putri Campus 1. While the object of research is student learning outcomes on Islamic Date material. This research uses classroom action research that is participatory, applicable, and collaborative and aims to improve the system, process, and learning situation. In this research instrument, data were collected using observation and tests. The results showed that the Magic Card learning media used was able to improve the ability of Islamic Date learning outcomes for class 1 Modern Islamic Institution Darussalam Gontor Putri Campus 1.